Legal Implications of De Facto State Recognition on Diplomatic and Consular Relations. - Saurav Kumar (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The recognition of de facto states remains one of the most contentious issues in contemporary international law, creating a complex web of legal ambiguities. This research examines the legal implications arising from the recognition or lack thereof of de facto regimes and its subsequent impact on diplomatic and consular relations. Using a normative legal research method with a statutory and conceptual approach, this study analyzes how the transition from de facto existence to partial or full recognition affects the application of the 1961 Vienna Convention on Diplomatic Relations and the 1963 Vienna Convention on Consular Relations. The findings suggest that while de facto states may exercise effective territorial control, their exclusion from the formal diplomatic community limits their ability to claim sovereign immunities and establish permanent diplomatic missions. Furthermore, this article explores the